Research on the influence mechanism of employees’ innovation behavior in the context of digital transformation - Wu, Jiale; Gong, Xiheng; Liu, Yijun (Frontiers in Psychology, 2022)
With the booming of digital economy, digital transformation has become an important initiative for the high-quality development of enterprises, however, in the process of digital transformation, the innovation performance of most enterprises will be reduced, and employee innovation, as the foundation of enterprise innovation, how to improve their innovation ability and guarantee the continuous innovation of enterprises has become a key issue. By conducting expert interviews and data crawling, the study uses rooting theory and Joya's method to sort out the influencing factors of employee innovation behavior in digital transformation enterprises, and uses the explanatory structural model to analyze the complex relationships among the influencing factors and establish a hierarchical structural model to organize and hierarchize them. The study shows that: leadership style, organizational innovation level, and organizational social responsibility are fundamental influencing factors, emotions and personality traits are direct influencing factors, and innovation expectations and innovation support feedback are important undertaking factors. The above findings provide theoretical guidance for companies to motivate employees to innovate and improve their innovation performance in the process of digital transformation.